REVISITING IDEOLOGIES IN ENGLISH LANGUAGE PEDAGOGY: SYSTEMATIC REVIEW OF HIGHER EDUCATION CONTEXT - Nirwana; Ramli; Sohaib Shafique; Wawan Gunawan; Yanty Wirza (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2026)
English language teaching (ELT) in higher education is increasingly shaped by global and ideological changes, particularly neoliberalism, standard language ideology, and the dominance of English in academic contexts. A review of studies published between 2015 and 2025 further shows that these concerns have gained significant prominence. This article draws on a systematic review of 47 Scopus-indexed publications. The data were analyzed using thematic synthesis to trace patterns, variations, and emerging trends, while VOSviewer was employed to visualize relationships among keywords, authors, and major research topics, allowing broader mapping of ideological orientations within ELT. The result shows that curriculum design, language policy, textbooks, and teaching materials remain key sites where ideology is reproduced. Classroom interaction and institutional practices also contribute to the reproduction of ideology, although less prominently than curriculum and teaching materials. Neoliberalism, standard language ideology, and internationalization appear as dominant orientations, whereas perspectives such as linguistic pluralism, translanguaging, and social justice function more as counter-discourses. Methodologically, most studies rely on qualitative approaches, particularly interviews, ethnography, case studies, and CDA. Other approaches, including mixed methods and frameworks like Systemic Functional Linguistics or autoethnography, are less frequently applied and tend to address more specific concerns. The findings of this study emphasize the importance of developing English teaching practices that are more inclusive and responsive to student diversity, through the application of linguistic pluralism and translanguaging. In addition, these results encourage critical studies that integrate micro (classroom interaction) and macro (policy and curriculum) analyses to understand ideological dynamics in higher education more holistically.